AWAN MAGNET PADA FASE MINIMUM AKTIVITAS MATAHARI DAN KAITANNYA DENGAN GANGGUAN GEOMAGNET - Clara Y. Yatini; Mamat Ruhimat (Jurnal Sains Dirgantara, 2011)
Interplanetary structures are important for the development of geomagnetic disturbance. The structures include intense north-southward Interplanetary Magnetic Field, the shock, solar wind density and velocity, and probably the magnetic cloud. We studied five events of magnetic clouds which occurred in the minimum phase of solar activity in order to understand solar wind-magnetosphere coupling. The correlations between storm intensity and the different solar wind parameters will also be presented as well. By analyzing five magnetic clouds occurred in 2006 and the associated geomagnetic enhancement, we found that not all magnetic clouds lead to geomagnetic disturbances. Keywords:Magnetic cloud, Interplanetary magnetic field, Geomagnetic disturbance